2010
DOI: 10.1002/ejoc.201000728
|View full text |Cite
|
Sign up to set email alerts
|

Trichlorosilane‐Mediated Stereoselective Reduction of C=N Bonds

Abstract: The reduction of C=N bonds represents a powerful and widely used transformation allowing new nitrogen‐containing stereocenters to be generated. Chiral amino groups are ubiquitous in a variety of bioactive molecules such as alkaloids, natural products, drugs, and medical agents, so the development of a catalytic stereoselective process for the preparation of enantiomerically enriched amines through ketoimine reduction is attracting increasing interest, especially in view of future industrial applications. Great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…[3] On the other hand, Lewis base based organocatalysts have been exploited with success in the stereoselective trichlorosilane-mediated reduction of N-substituted ketoimines [4] and in the asymmetric Biginelli reaction. [5] The hydrosilylation reaction is a widely employed method for accessing enantiomerically enriched amines, [6] and it is extremely useful from an industrial perspective, as it affords chiral products by using typically very cheap reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…[3] On the other hand, Lewis base based organocatalysts have been exploited with success in the stereoselective trichlorosilane-mediated reduction of N-substituted ketoimines [4] and in the asymmetric Biginelli reaction. [5] The hydrosilylation reaction is a widely employed method for accessing enantiomerically enriched amines, [6] and it is extremely useful from an industrial perspective, as it affords chiral products by using typically very cheap reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…10 The reaction with trichlorosilane in the presence of catalytic amounts of a chiral Lewis base is a well-established. 11 In the last decade different classes of enantiomerically pure Lewis bases have been developed. 12 We started our investigation by screening different typologies of chiral activators, developed by us and other groups.…”
mentioning
confidence: 99%
“…Since the first chiral Lewis-base derived catalyst was reported in 2001, 1 there have been many variants of catalyst prepared and evaluated; 2,3 selected examples include formamides, [4][5][6][7] sulfinimides, 8,9 pyridines, [10][11][12] and organophosphorus compounds. [13][14][15] The main focus of research from this group has been using an imidazole derived catalyst that has been shown to function as efficiently as the reported analogous picolinoyl series, 16 in addition to being amenable to reductive amination protocols.…”
Section: Introductionmentioning
confidence: 99%